Lutar, construir, reforma agrária popular: análise da aproximação entre um movimento social e o comércio tradicional de alimentos - Petrasi, Pilar (Universidade do Vale do Rio dos Sinos, 2023)
This master's dissertation aimed to analyze the legitimization process of the Movimento Sem Terra (MST) as it enters the traditional food market from a decolonial perspective. The study sought to identify the strategies employed by the Movement, analyze consumer perceptions, and explore the inherent tensions arising from the convergence of a social movement advocating for land reform with the logics of the capitalist market. Decolonial theoretical frameworks were chosen because they understand that the conditions leading to the creation of the MST were shaped by a historical and economic context that produced persistent social issues that still need addressing. Furthermore, the MST's own identity demands such an approach since the Movement has constructed and preserved its distinct ethos. Legitimation theories and contested markets were relevant for comprehending and exploring the strategies adopted by the MST to ensure its economic viability, strengthen its agenda, and gain visibility across various sectors of society. The study utilized a qualitative multimethod approach. The analysis revealed that, although still a contested movement, the MST is undergoing a process of legitimization. As an economic venture, the Movement employs transmodern approaches, which contribute to strengthening its legitimacy as a differentiation strategy. Lastly, the study calls for a debate on the social role of markets and underscores the importance of advancing future studies to support the construction of new social realities.
Keywords: Movimento Sem Terra; Mercado; Comércio de alimentos; Transmodernidade; Market; Food trade; Transmodernity; ACCNPQ::Ciências Sociais Aplicadas::Administração